The Ideological Recontextualisation of Modern Fatherhood in Scandinavian and British Nordic Noir Crime Series - Eli Løfaldli (Modern Languages Open, 2022)
Nordic Noir crime series have enjoyed much popularity and positive critical attention in Britain, as have many other aspects of Scandinavian ways of life, and the extent and nature of this cultural curiosity in the years following the international release of the originary 'Forbrydelsen/The Killing' (2007) deserves further analytical attention. This article investigates one important manner in which culturally specific and ideologically charged content was received and negotiated in Britain in this period by comparing how conceptions of modern fatherhood are expressed in Scandinavian crime drama and British adaptations of the Nordic Noir crime genre. Nordic Noir series based in both cultures can be seen to share a strong thematic focus on fatherhood, especially centred on characters that embody features associated with openly affectionate and hands-on fatherhood, or “modern dads”. However, there are notable differences in how the figure of the modern dad is represented in Scandinavian crime drama and British series that appropriate key genre features of Nordic Noir, which suggests that the construct has undergone what is termed “ideological recontextualisation”. The Scandinavian modern dad characters tend to be heroes, their capacity for involved, selfless love and care for their children unproblematised and uncontested within the story worlds, while their British counterparts are far more suspect entities. Their seemingly close and loving interaction with children may be potentially sexually motivated, immaturely or selfishly handled, or even serve to mask their criminal intent, and they typically turn out to be the villains of the stories. The Scandinavian ideology connected to modern fatherhood appears, then, to have been an object of both fascination and contestation in British culture in this period, and may have been more resistant to undisputed cultural importation than female main characters with attachment issues and woolly jumpers.